Research of estimation algorithm's characteristics of controlled flight trajectory - Харченко, В. П.; Васильєв, В. М. (Proceedings of National Aviation University (archive), 2021)
The outcomes of a research and statistical simulation of algorithm of trajectory estimation are given. This algorithm is able to imitate flight management and to form control signals in the correspondence with the actual laws, with nonlinear functions of restriction of signals. The algorithm has a high exactitude of trajectory estimations and allows avoiding the estimation divergence while maneuvering.